PERAN PEMERINTAH INDONESIA DALAM MELINDUNGI HAK PEKERJA MIGRAN INDONESIA SEBAGAI PEKERJA RUMAH TANGGA DARI PRAKTIK UPAH YANG TIDAK DIBAYAR DI MALAYSIA - Aulia Purnama Ramadhan; Evi Deliana; Zulfikar Jayakusuma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Domestic Workers are the occupational sector that dominates Indonesian MigrantWorkers. In line with the increase in sending Indonesian Migrant Workers, cases of unpaidwage to domestic workers according to the provisions also increase every year. The problemof unpaid wage in accordance with the provisions of domestic workers still persists to thisday and is most prevalent in the placement country of Malaysia. This type of research isnormative law. The analysis carried out is a qualitative analysis or research that is stated inwriting.From the results of the problem research, it was found that First, the role of theMinistry of Foreign Affairs and the Ministry of Labour in overcoming the problem ofunderpayment is to form regulations, and regional cooperation to discuss rights &obligations as well as wage standards. Second, BP2MI and Migrant Care's efforts in dealingwith the problem of substandard wages are to provide advocacy, assistance both within thecountry and in the recipient country of the worker. Author's suggestion, First, it is hoped thatthe Ministry of Foreign Affairs together with the Ministry of Manpower can optimize therules and agreements regarding wage for domestic workers and their supervision specificallyand monitored. Second, there is a need for a special unit to be formed by BP2MI and MigrantCare which specifically adjudicates the wage of domestic workers who are not paidaccording to the provision.Keyword: Ministry of Foreign, Ministry of Labour, BP2MI, Migrant Care, Yurisdiction,Passive National, Migrant Worker, Wage, Malaysia.